Assessing Malay Proficiency at the Tertiary Level: Criteria Features in Learner Language - Jyh Wee Sew (Kajian Malaysia, 2015)
Despite the variations in verbal interaction, the standard of evaluation for summative assessment is somewhat straightforward in foreign language education. The consensus on what is foreign language proficiency is typically based on first language (L1) proficiency. The introduction of criteria features indicative of learner proficiency based on second language learner English corpora, in a recent study from Cambridge, suggests that differentiating learner grammar from standard grammar may be an agenda in language evaluation. Criteria features are useful to ascertain if a foreign language learner has attained an expected proficiency unique to the learning environment and if the examinable learning outcome is distinguishable as an A or a B or a C, etc. in the standard gradation of language assessment. This discussion highlights certain positive features identifiable as basic characteristics of learner proficiency in Malay. Differing from current standard L1 grammars that are derived from contemporary discourses of mass media, the Malay criteria features presented in the discussion are based on learner language. The Malay criteria discussed may initiate a prototype towards the schemata befitting the assessment of Malay proficiency unique to beginners in foreign language education.